PERANCANGAN KONTEN TIKTOK SEBAGAI MEDIA PROMOSI EDUKATIF PRODUK UMKM D’KLOTIQ KLOMPEN BATIK ETNIQ - Setyaji Safa Bharanatya; Emmalia Adriantantri; Reiny Ditta Myrtanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of short-video social media has encouraged the use of digital platforms as educational and promotional media. Many local cultural-based micro, small, and medium enterprises (MSMEs) have not optimally utilized TikTok to introduce cultural values embedded in their products. This study aims to design TikTok video content as an educational promotional medium for D’Klotiq Klompen Batik Etniq, a local MSME producing batik-based wooden footwear. This research employed the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, expert validation, and questionnaires distributed to TikTok users aged 18–25 years. The results show that the developed TikTok video content, which highlights the handmade production process, batik motifs, and cultural storytelling, received very good validation results from experts and positive responses from users. The study concludes that TikTok content can function effectively as an educational promotional medium that introduces local cultural values while increasing public awareness of MSME products.